Spillover risks on cryptocurrency markets: A look from VAR-SVAR granger causality and Student's-t Copulas - Toan Luu Duc Huynh (Journal of Risk and Financial Management, 2019)
This paper contributes a shred of quantitative evidence to the embryonic literature as well as existing empirical evidence regarding spillover risks among cryptocurrency markets. By using VAR (Vector Autoregressive Model)-SVAR (Structural Vector Autoregressive Model) Granger causality and Student's-t Copulas, we find that Ethereum is likely to be the independent coin in this market, while Bitcoin tends to be the spillover effect recipient. Our study sheds further light on investigating the contagion risks among cryptocurrencies by employing Student's-t Copulas for joint distribution. This result suggests that all coins negatively change in terms of extreme value. The investors are advised to pay more attention to 'bad news' and moving patterns in order to make timely decisions on three types (buy, hold, and sell).
Keywords: C46; F38; G01; 330; Bitcoin; cryptocurrency; spillover risks; Copulas; Student's-t